The relationship of security needs with irrational beliefs among medical students - I. I. Koryagina; V. G. Maralov; V. A. Sitarov (Образование и наука)
Introduction. Irrational beliefs as distortions in the perception of reality are characteristic of the representatives of many professions, including medical professionals. Effective work to overcome them, which should begin at the training stage, can be carried out only if the nature of the relationship between irrational beliefs and different factors, where needs, including security needs, playing an important role, is identifiedAim. The current research aims to identify the relationship between security needs and irrational beliefs among medical students.Research methodology. The authors tested the hypothesis of the relationship between the need for danger and the beliefs of the antisocial and aggressive types, the need for security with the beliefs of the dependent and avoidant types, the need for security with the beliefs of the obsessive-compulsive type, taking into account the gender and age of students. The study involved 277 (70 males and 197 females) junior and senior students of the Ivanovo State Medical Academy, with an average age of 19.25 ± 2.41 years old. As a diagnostic tool, the questionnaire developed by the authors was used to identify the needs for danger and safety as well as a list of irrational beliefs of A. Beck and A. Freeman.Results and scientific novelty. As a result, it was found that there were no significant differences in the studied parameters among both men and women. Both of them showed a positive relationship of irrational beliefs of the obsessive-compulsive type with the need for safety and a negative relationship with the need for danger, and beliefs of the dependent type – with the need for safety. Differences were found depending on the age. The need for security was negatively associated with anti-social beliefs among first-year students, and with passive- aggressive beliefs among senior students. The need for security among first-year students is positively correlated with the beliefs of the dependent type, and among senior students – with the beliefs of the avoidant type.Practical significance. The results obtained significantly supplement the data available in psychology on the role of irrational beliefs in meeting security needs. The research findings can also be used in the process of professional training of future medical students as well as in the work of the psychological service of universities.